USE OF INTERACTIVE DYNAMIC MODELS IN ILLUSTRATIVE DISPLAY OF DRAWINGS (Academia Science Repository, 2023)
The article describes the didactic possibilities of interactive dynamic models and methodological recommendations for their use in the educational process.